Apoptotic induction of ribosome-inactivating proteins (RIPs) isolated from Carica papaya L. leaves on cancer cell-lines - ., Sismindari; ., Rumiyati; I.A., Ida Ayu Putu Indah; Enstini, Ni Luh Putu Yulina (Indonesian Journal of Pharmacy, 2009)
Carica papaya L. leaves are potential for cancer treatment, this is due to the presence of Ribosome-inactivating proteins (RIPs), which demonstrated a cytotoxic effect on cancer cell lines. Therefore, this research was done to find out the effect of protein fraction containing RIPs isolated from C. papaya in the induction of apoptosis on cancer cell-lines (Raji and myeloma cell-lines).The protein fraction was isolated from Carica papaya L. leaves using ammonium sulphate precipitation and analyzed the activity on supercoiled double stranded DNA cleavage, in order to identify the presence of RIP. The active fraction called ‘CP protein’, was then analyzed on the induction of apoptosis by double staining method using acrydin orange-ethidium bromide, followed by analyzing the expressions of p53 and bcl2 using immunocytochemistry.The results demonstrated that the CP protein possessed cytotoxic activities on myeloma and Raji cell-lines with the IC50 of 1.80 mg/mL and 2.49 mg/mL respectively. Late apoptosis was detected on myeloma but not on Raji cell lines which was incubated with 0.9 mg/mL and 0.6 mg/mL of CP proteins respectively. In addition, the protein was able to increase the expression of apoptotic regulatory protein, p53, on myeloma cell-line and almost undetected on Raji cell-line.Key Words : Ribosome-inactivating proteins (RIPs), Carica papaya L. , expression of p53 and Bcl-2, myeloma cell-line, Raji cell-line.